Analysts' experience and interpretation of discretionary accruals in predicting future earnings. (September 2017) - Liu, Alfred Zhu; Schneible, Richard
Abstract: Our paper investigates whether analysts' experience mitigates their forecast over-optimism associated with high discretionary accruals. Prior literature shows that analysts' forecast optimism is associated with high total accruals and working capital accruals, and this forecasting inefficiency can be mitigated by analysts' experience. We extend this line of research by first showing that forecast over-optimism is associated with higher discretionary accruals. We then show that analysts' experience with the related industry and their experience of decomposing earnings into cash flows and accruals appear to mitigate analysts' over-optimism related to discretionary accruals while analysts' firm and general experiences do not. Our study provides new evidence on how experience affects analysts' use of discretionary accruals.